The Role of CSR in Moderating the Factors that Affect Firm Value in State-Owned Enterprises (SOEs) in Indonesia - Citradewi, Adelina; Febriana, Ismi Nur (Universitas Sumatera Barat, 2025)
This study aims to examine the influence of profitability, liquidity, and leverage on firm value and to investigate the moderating role of corporate social responsibility (CSR) in these relationships. The research employs a quantitative approach and is classified as descriptive. The population consists of state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The sampling technique used is purposive sampling, with specific criteria applied to obtain a total of 62 samples. Following the classical assumption tests, the normality test indicated that the data were not normally distributed and that outliers were present. Using EViews 12, a total of 5 outliers were identified, resulting in 57 usable samples. The data analysis techniques applied include panel data regression and Moderated Regression Analysis (MRA). Hypothesis testing is conducted through the coefficient of determination (R²), partial test (t-test), and simultaneous test (F-test), using EViews 12 software. The results show that profitability has a significant positive effect on firm value, while liquidity does not have a significant effect. Leverage is found to significantly affect firm value. Additionally, CSR does not moderate the relationship between profitability and firm value, liquidity and firm value, nor leverage and firm value. These findings suggest that financial performance indicators such as profitability and leverage are more influential on firm value, while CSR disclosure may not necessarily enhance the impact of these variables.